KEPERCAYAAN MEREK, KUALITAS LAYANAN DAN PENGARUHNYA TERHADAP LOYALITAS NASABAH BANK CIMB NIAGA DI SURABAYA - Mochamad Afif (Journal of Business & Banking, 2012)
Customer loyalty is one of the factors that influence the level of sales company. It has been the fact that every company tend to compete in order that they can perform a variety of strategies to establish a customer loyalty. In the banking sectors, the banks are also doing a lot of strategies to increase customer loyalty. In this research, there are two factors that can affect customer loyalty, brand trust and quality of services. The purpose of this study is to examine the effect of brand trust and quality services to customer loyalty. This research was conducted in Surabaya where the customers of Bank CIMB Niaga were used as the place for the research. The datawere collected from the respondents in this bank. It attained 110 respondents and these customers. The data were analyzed by using multiple regressions with SPSS 16.0 for windows. The results showed that brand trust and service quality significantly influence the customer loyalty Bank CIMB Niaga in Surabaya Some suggestions were also asserted in connection with these results both for the researchers and the instrument.